PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK PADA MATA PELAJARAN PKn MATERI MENGENAL KERAGAMAN BUDAYA DI INDONESIA KELAS III SD NEGERI TUKANGAN YOGYAKARTA - Ratna Sari, Hesti; Sutrisna Wibawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
PKn learning in elementary schools tends to still seem boring and theoretical. Therefore, researchers tried to design more interesting learning by designing learning materials that were adapted to the characteristics of class III students. It is hoped that flipbook learning in the PKn subject, the material Understanding Cultural Diversity in Indonesia, can increase the effectiveness of learning, strengthen understanding of the concept of citizenship, and have a positive influence on student learning motivation. This research and development resulted in the creation of flipbook media for Class III PKn educational content in elementary schools. This development refers to five phases: analysis, design, development, implementation, and evaluation which is called ADDIE. The conclusion of this research and development shows that the development of flipbook media in the PKN subject, Getting to Know Culture in Indonesia, class III elementary school, was successfully implemented according to the ADDIE level.